Predictive Value of Total Serum Bilirubin within 6 Hour of Birth for the Development of Hyperbilirubinemia After 72 hours of Birth - Bandi, Chaitra (J Clin Diagn Res, 2016)
INTRODUCTION: Neonatal jaundice is benign and no intervention might be required, but jaundice can be associated with an underlying disease condition, which therefore warrants accurate and unbiased estimation of bilirubin. Total Serum Bilirubin (TSB) measurements (at discharge between 18 hours and 72 hours) can be used to predict the chances of developing severe hyperbilirubinemia. MATERIALS AND METHODS: The present hospital-based prospective study was undertaken to determine the predictive value of serum bilirubin before 6 hours of life for subsequent hyperbilirubinemia in healthy term neonates. One hundred and fifty healthy term newborns delivered during January 2013–December 2013 at Hanagal Shri Kumareshwara Hospital and Research Centre, S. Nijalingappa Medical College, Bagalkot Karnataka, India, were included in the study. Serum bilirubin levels were estimated twice, first, within 6 hours of life and second, after 72 hours of life. Bilirubin values were plotted on previously published nomograms. Sensitivity, specificity of the test was established. RESULTS: A measure of TSB levels (within 6 hours of life) across the study population, showed that maximum number of infants (70/150) had TSB level between 4.1 and 5.5 mg/dL and 16 infants had TSB level >5.6 mg/dL. The TSB levels (after 72 hours of life) showed that maximum newborns (83/150) had TSB levels between 12.8 and 15.3 mg/dL and 9 infants had TSB levels between 7.7 and 10.2mg/dL. Eighteen infants developed hyperbilirubinemia. Newborns with TSB value of >4.95mg/dL within 6hours of life had developed significant hyperbilirubinemia after 72 hours of life with sensitivity of 100% and specificity of 89% (p=0.0001), which was highly statistically significant. CONCLUSION: A TSB level of >5 mg/dL within 6 hours of birth would serve as a predictor for risk of subsequent hyperbilirubinemia in the near future.